Control over Stereogenic N–N Axes by Pd-Catalyzed 5-endo-Hydroaminocyclizations - Hutskalova, Valeriia; Sparr, Christof (Synthesis, 2023)
A novel approach for the stereoselective construction of N–N atropisomeric compounds by a Pd-catalyzed 5-endo-hydroaminocyclization is described herein. A broad range of bisheterocycles , connected by a configurationally stable N–N stereogenic axis, were prepared with catalyst control in enantioenriched form.
Keywords: palladium; cyclization; heterocycles; asymmetric catalysis; alkynes; atropisomers